A systematic review of biocultural innovation: Challenges, potentialities and agendas for environmental futures - Juan David Reina Rozo (Journal of Agriculture and Environment for International Development)
Biocultural diversity and heritage are areas threatened by the implications of the development agenda. They study the interdependent relationships between people and the biodiversity of Indigenous and Local community's territories. There are innovation practices related to biocultural memory, heritage, and diversity for rural development. This article systematically reviews the literature around the concept of Biocultural Innovation (BcI) following the PRISMA protocol. The databases Scopus, Web of Science, and Google Scholar were used to select the records between 2012 and 2023. Of the 71 records identified, a total of 33 documents met the exclusion/inclusion requirements, including 21 publication sources, 78 authors, 41 institutions, and 18 countries. Relevant case studies and programs that have promoted the application of BcI, particularly in the Global South, are also identified. A qualitative assessment is made to argue for the relevance of this concept based on its challenges and potential. Biocultural innovation is an emerging area of inquiry that provides elements to guide policymakers, research institutions and communities wishing to develop approaches to protect, sustain and revitalize rural place-based innovation. Finally, suggestions for future research are made.